2017
DOI: 10.1177/1054773817708933
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Is Linked to Nursing Workload in a Singapore Hospital

Abstract: No studies have examined the association between patient satisfaction and the allocation of nursing care hours using a workload management system. The aim of this study is to examine the correlation between inpatients' perceived satisfaction with nursing care and nursing workload management in a Singapore hospital. A secondary data analysis was performed based on the results of 270 patients' perceived satisfaction measured by the Revised Humane Caring Scale and nursing workload management data extracted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…Patient satisfaction with nursing work is regarded as a sensitive indicator of nursing outcomes. 45 Previous studies have shown that nurses’ optimistic moods will contribute to patients feeling more positive emotionally. 46 Sahu’s 47 research points out that nurses who engaged in rotating shift work, especially night work, were the most prone to impairment of work efficiency, which affected patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction with nursing work is regarded as a sensitive indicator of nursing outcomes. 45 Previous studies have shown that nurses’ optimistic moods will contribute to patients feeling more positive emotionally. 46 Sahu’s 47 research points out that nurses who engaged in rotating shift work, especially night work, were the most prone to impairment of work efficiency, which affected patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…the number of patients for each nurse and nursing technician, the greater the average stay of patients and the occurrence of urinary tract infection related to invasive procedures and the lower the satisfaction rate regarding nursing care (16) . Similarly, a significant correlation was found between the workload of the nursing team and patient satisfaction (5) .…”
Section: Discussionmentioning
confidence: 73%
“…Some studies demonstrate how these attributes affect patient satisfaction. A positive correlation was found between patient satisfaction and participation in care (5) . In a workload analysis, this study revealed that the hours nurses dedicated to their work did not meet the needs of communication and the information patients received was insufficient, indicating a low level of patient satisfaction in relation to the communication and participation attributes in the care.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As most surgical patients are also discharged from the hospitals within shorter time periods, this makes it more challenging for the ward nurses to incorporate patient education into their busy schedules (Yeh, Wu, & Tung, 2018). In the face of limited manpower and when the nurse‐to‐patient ratios are maximized, these ward nurses are therefore compelled to reduce their caring behaviours to accomplish the more acute tasks and prioritize nursing care activities that could reduce patient risks and prevent deteriorations (Ball, Murrells, Rafferty, Morrow, & Griffiths, 2014; Goh, Ang, Chan, He, & Vehvilainen‐Julkumen, 2018; White, Jackson, Besner, & Norris, 2015). Unless judicious efforts are further implemented to improve the existing practice standards to prioritize patient education, it is foreseen that the ward nurses will remain task‐oriented and rarely take on more proactive roles.…”
Section: Discussionmentioning
confidence: 99%